Efeitos da adição de aminoácidos essenciais livres à dieta e da ausência de nutrientes na atividade de enzimas digestivas e no metabolismo intermediário de juvenis de matrinxã (Brycon amazonicus) - Camilo, Rodrigo Yamakami (2007)
For the nutrients ingested by fish are used for growth and maintenance of the energetical metabolism, they need firstly being absorbed by gastrointestinal tract. However, the most foods ingested cannot be absorbed directly through the gastrointestinal mucosa, since they are largely formed by high molecular weight molecules. The process of transforming large molecules into smaller is catalyzed by digestive enzymes. Therefore, a limiting factor to the food absorption is the availability of those enzymes. Their synthesis and the secretion can be stimulated by free amino acids in the gastric and intestinal lumen. We have investigated the effect of free essential amino acids (AAEL) supplementing the diets on the synthesis of digestive enzyme and the intermediary metabolism of matrinxa. Six fish groups were submitted to different feeding condition for 15 days. The control group was fed with 34% of protein and 4.670 kcal of gross energy by kg of food. Maize starch and soy oil were used as energy source. The second group, called SO, was fed with casein and gelatin as protein source and maize starch as energy source. The third group, called SO+AAEL, was feed with a similar food wherein the 0.6% of cellulose, added as inert stuff, was replaced by a mixture conteining 0.1% of phenylalanine, 0.1% tryptophane, 0.1% valine, 0.1% histidine, 0.1% arginine and 0.1% leucine. The fourth group, called SA, was feed with casein and gelatin as protein source and soy oil as energy source. The fifth group, called SA+AAEL, was feed with a similar food but 0.6% of cellulose was replaced by a mixture of six AAEL, just as above. The last group was kept in fast over the experimental period. After the experimental period, 9 fish from each treatment were sampled. The blood was withdrawn and white muscle, liver and digesting treat were excised. The amylolytic, proteolytic and lipolytic activities assayed in digestive tract homogenates were responsive to diet composition, mainly to the absence of starch and the addition of FEAA. The present set of data indicates that the matrinxa is able to adjust these enzymes production toward digestive process optimization. The alterations in plasmatic, muscular and hepatic metabolic intermediaries concentration become evident that the matrinxa is able to adapt its intermediary metabolism to the changes on the feeding condition to preserve vital functions. However the increase of the enzymatic activity in the fed with the diet AAEL did not result in significant modification on the intermediary metabolism.